Individual Profiles of Psychological Capital in a Spanish Sample - Djourova, Nia Plamenova; Rodríguez, Isabel; Lorente-Prieto, Laura (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
Psychological Capital (PsyCap) consists of hope, self-efficacy, resilience and optimism. It is usually assumed that individuals score similarly across these four components, however, there have been suggestions in the literature that in some cases, people can score high on some dimensions and low on others, and that it is necessary to explore the matter further (Dawkins, 2014). Hence, the main objective of this article is to explore if the relationship between the dimensions of PsyCap results in individual profiles; to see which sociodemographic characteristics they have, and how the profiles relate to job satisfaction and performance. The sample consists of 1752 employees from different companies in Spain. We used Latent Profile Analysis and the results revealed that a four-profile model is the best fit for our data, where Profile 1 was characterized by low self-efficacy and hope, and high resilience and optimism; Profile 2 by high self-efficacy and hope, and low resilience and optimism; Profile 3 by low self-efficacy and high hope, resilience and optimism; and Profile 4 by high scores on all PsyCap constructs. The majority of the sample was classified in Profile 4, showing support for the unitary structure of PsyCap. However, for some individuals scores differed across the four PsyCap dimensions. Furthermore, there were high-low and low-high configurations for hope and self-efficacy on the one hand, and resilience and optimism on the other. Lastly, our results emphasize the combination of hope and self-efficacy as important contributors to employee outcomes.